2014
DOI: 10.1386/eta.10.1.99_1
|View full text |Cite
|
Sign up to set email alerts
|

Developing thinking skills through the visual: An a/r/tographical journey

Abstract: This article reports on research that investigated how students’ critical thinking skills can be developed through images. The research was located in New Zealand, a country whose national curriculum and assessment systems stress ‘thinking’ as a key competency and place emphasis on developing visual literacies. The research was underpinned by a critique of the impact of images on students living in an image-saturated world and the importance of them being visually literate. It involved examination and document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Smith and Lazo's (2014) research one of them on Developing thinking skills through the visual: an a / r / topographical journey, where this research emphasizes 'thinking' as the main competency and emphasizes visual literacy development. This study showed that students' critical thinking skills could be developed through visuals [12]. According to the use of software, the use of the Internet of Things (IoT) also affects students' thinking skills.…”
Section: Discussionmentioning
confidence: 96%
“…Smith and Lazo's (2014) research one of them on Developing thinking skills through the visual: an a / r / topographical journey, where this research emphasizes 'thinking' as the main competency and emphasizes visual literacy development. This study showed that students' critical thinking skills could be developed through visuals [12]. According to the use of software, the use of the Internet of Things (IoT) also affects students' thinking skills.…”
Section: Discussionmentioning
confidence: 96%
“…The experts' evaluation resulted in the Critical Thinking Test for Basic Education (CTTBE) that was applied for testing to a group of students identical to the one that participated in this study. From these procedures resulted a test consisting of 48 items with visual stimuli printed in color (Downey, 2009;Facione, 1990;Gelerstein et al 2016;Joglar, 2015;Lazo & Smith, 2014) and verbal stimuli, i.e., short texts with authentic situations (Bonk & Smith, 1998;Care et al, 2018;Evans, 2020;Halpern, 1998). The items assess the following skills:…”
Section: Instrumentsmentioning
confidence: 99%
“…The visual has been used to transmit constructs and ideas. Lazo and Smith (2014) examined the use of images to promote increase in critical thinking skills with students in a secondary school setting. A component of this research that is very relevant to the current study was inclusion of visual culture as "visual manifestations that belong to students' everyday lives to illustrate how there reading of these images interpret final meaning?"…”
Section: Learning Enhancementmentioning
confidence: 99%